Implementing a Distributed System as a Solution to Problems in the Indosat Cooperative - erman arif (Institut Pendidikan Indonesia, 2019)
Distributed System is a system where the hardware or software components are located in a computer network and communicate with each other and coordinate using message parsing. In this study, interviews will be conducted to analyze and evaluate the system that runs in the Indosat Cooperative. The purpose of this research is to overcome the constraints of systems that are separated by clustering and pooling resources (in this case computational resources), into a coordinated combined system with a capacity that far exceeds the capacity of the individual components. Keywords- Distributed system, analysis, Indosat Cooperative